Municipal democracy: development trends in the materials of law enforcement practice - Ekaterina S. Shugrina (Правоприменение)
The subject. The article analyzes the trends of community participation in the implementation of local self-government.The purpose of the paper is to confirm or disprove hypothesis that the involvement of the population in the implementation of local self-government determines the genuine implementation of municipal legal acts and contributes to finding effective solutions to local issues.The research was carried out with use of main scientific methods (analysis, induction and deduction), special (statistical) method as well as the method of interpretation of the legal acts.The main results and scope of their application. The same form of direct democracy is mentioned in different Russian laws by different words often. The concept and requirements for the same forms, the limits of their application, the implementation procedures are described in different ways. There is a significant shift in emphasis in the use of various forms of direct democracy at the municipal level. In reality, the ability of local residents to exercise local self-government is significantly reduced. The involvement of the population is increasingly declared as an additional investment tool. The analysis of law enforcement practice shows the emergence of new forms of participation of citizens in the implementation of local self-government, which either do not have proper legal regulation, or it is fragmentary, carried out mainly by bylaws. The majority principle was the basis of decision-making in Russia for a long time, including the Soviet period, i.e. the decision was made on the basis of the opinion of the majority or qualified majority; the minority obeyed the majority. It has become urgent to develop new legal structures to identify and take into account the opinion of the minority in recent years.Conclusions. The involvement of the population in the implementation of local self-government is a criterion that the norms provided for in the texts of normative legal acts are really beginning to be implemented, the population is increasingly beginning to use them. If citizens lack legal instruments, they initiate their development and adoption in the form of relevant regulatory legal acts or other legal documents. The institutions of power and civil society do not replace each other, but promote mutual harmonious development aimed at improving the quality of life of citizens.